High throughput FPGA Implementation of Data Encryption Standard with time variable sub-keys - Soufiane Oukili; Seddik Bri (Institute of Advanced Engineering and Science, 2016)
The Data Encryption Standard (DES) was the first modern and the most popular symmetric key algorithm used for encryption and decryption of digital data. Even though it is nowadays not considered secure against a determined attacker, it is still used in legacy applications. This paper presents a secure and high-throughput Field Programming Gate Arrays (FPGA) implementation of the Data Encryption Standard algorithm. This is achieved by combining 16 pipelining concept with time variable sub-keys and compared with previous illustrated encryption algorithms. The sub-keys vary over time by changing the key schedule permutation choice 1. Therefore, every time the plaintexts are encrypted by different sub-keys. The proposed algorithm is implemented on Xilinx Spartan-3e (XC3s500e) FPGA. Our DES design achieved a data encryption rate of 10305.95 Mbit/s and 2625 number of occupied CLB slices. These results showed that the proposed implementation is one of the fastest hardware implementations with much greater security.